Forage Substitution with Media Plant White Oyster Mushroom Waste Fermented to Percentage of Local Sheep Carcass - Rindu Awalia Tarigan; Tri Hesti Wahyuni; Hamdan .; Iskandar Sembiring; Nurzainah Ginting (Universitas Sumatera Utara, 2018)
RINDU AWALIA, 2018: “Forage Substitution with Waste Media for White Oyster Mushroom Planting Fermentation on Percentage of Carcass at Local Sheep”. Supervised by TRI HESTI WAHYUNI and HAMDAN. The study aimed to determine the percentage of carcass in local sheep given the waste of fermented white oyster mushroom growing media as an alternative feed, carried out in NamoTrasi Village, Pasar VIII, October - December 2017. Using local sheep the average initial weight was 9 ± 0.25 kg. The design used was a completely randomized design (CRD) with 4 treatments and 5 replications namely P0 = grass 60% + concentrate 40%. P1, P2, and P3 respectively are 45%, 30%, 15% grass, and fermented white oyster mushroom planting media waste 15%, 30%, 45% and 40% Concentrate. The results showed that the slaughter weight (kg / head) was: 13.67; 13,92; 13,81; and 13.78. Empty body weight (kg / tail): 8.98; 9,16; 9,10; and 9.01. Carcass weight (kg / head): 5.23; 5.40; 5,34; and 5.17. In the percentage of carcass (%): 58.12; 58.97; 58.52; and 57.33. So it can be concluded that the waste of fermented white oyster mushroom growing media can substitute forage as a feed for local sheep but cannot increase the percentage of carcass component. Keywords: Waste of white oyster mushroom planting media, fermentation, carcass, local sheep.